2005
DOI: 10.1002/path.1699
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of dendritic cells in oral lichen planus

Abstract: Using immunohistochemistry the presence of different dendritic cell (DC) subsets was analysed in 16 biopsies from patients with oral lichen planus (OLP). A significant increase of CD1a+/Langerin+ Langerhans cells, DC-SIGN+ DC and CD123+/BDCA2+ plasmacytoid DCs (PDCs) was found in the epithelium and in the stroma of OLP biopsies compared to normal oral mucosa. A proportion of DCs were mature DC-LAMP+ and expressed S100 or CD11c, typically found in the interdigitating DCs of nodal T-cell areas. Double staining r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
88
1
16

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 54 publications
14
88
1
16
Order By: Relevance
“…Over time, the spectra of effects of LCs on peripheral T cells, activation of skin resident memory T lymphocytes, a defense function against pathogens and tissue repair were explored [72,73]. In our study, immunohistochemical results of S100 staining observed in the case of classic LPP and LP, both intraepithelial LCs and dermal DCs, are consistent with the results of Santoro et al [49]. However, significant differences between the groups were not found by us, and this might indicate the similarity existing between clinical forms of LP.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Over time, the spectra of effects of LCs on peripheral T cells, activation of skin resident memory T lymphocytes, a defense function against pathogens and tissue repair were explored [72,73]. In our study, immunohistochemical results of S100 staining observed in the case of classic LPP and LP, both intraepithelial LCs and dermal DCs, are consistent with the results of Santoro et al [49]. However, significant differences between the groups were not found by us, and this might indicate the similarity existing between clinical forms of LP.…”
Section: Discussionsupporting
confidence: 81%
“…Acting as paracrine and autocrine mediators, these have been shown to be involved in numerous intracellular and extracellular functions, such as regulation of cell proliferation and survival or, alternatively, apoptosis, chemotaxis, inflammation, immune responses, Ca 2+ homeostasis, differentiation of keratinocytes and dynamics of cytoskeleton constituents [45,46,47]. S100 proteins are expressed in normal and diseased skin [48,49], and the subcellular distribution of these proteins in keratinocytes is heterogeneous [50,51]. S100-positive dendritic cells (DCs), involved in antigen presentation, phagocytosis, healing and repair processes, have been demonstrated to be significantly increased in LP [52].…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate Texas red-and FITC-conjugated isotype-specific secondary antibodies were used to reveal the primary antibodies, as previously described. 18,24 Immunostained sections were analyzed and photographed using an Olympus BX60 fluorescence microscope, equipped with the Olympus DP-70 digital camera. Pictures were analyzed by Analysis 3.2 soft imaging system GMBH and Adobe Photoshop 5.0, limited edition.…”
Section: Tissues and Reagentsmentioning
confidence: 99%
“…24 Since the number of ChemR23 ϩ cells regularly outnumbered CD56 ϩ and CD94 ϩ cells, the expression of ChemR23 by DCs was also investigated. Figure 6 shows that OLP lesions presented an elevated number of CD123 ϩ , BDCA2 ϩ plasmacytoid DCs, and DC-SIGN ϩ myeloid DCs.…”
Section: Role Of Chemerin In the Colocalization Of Nk Cells And DC Inmentioning
confidence: 99%
“…In this work, we focused our analysis on two representative oral areas: the buccal mucosa, covering the inside of the cheek, and the lining mucosa anterior to the murine incisors, including the gingival papilla and the mucosa toward the midline of the lower lip (hereinafter termed lining mucosa). These anatomically distinct tissues contain DC subsets that were found to be involved in various oral diseases such as lichen planus and periodontitis (29,30). We believe that by studying these oral DCs, we can increase our understanding of their role during disease and harness their capacity for eliciting protective oral immunity.…”
mentioning
confidence: 99%